Radioembolization with Yttrium-90 microspheres for patients with unresectable hepatocellular carcinoma - Bhangoo, Munveer Singh (J Gastrointest Oncol, 2015)
BACKGROUND: Hepatocellular carcinoma (HCC) is aggressive primary malignancy of the liver that most commonly presents late in the disease course. As a result, the majority of patients are not candidates for curative therapies. Locoregional therapies including Yttrium-90 (Y-90) radioembolization play an important role in management of the vast majority of patients with HCC. METHODS: Patients with unnresectable HCC (n=17) treated with Y-90 radioembolization from 2005 to 2014 were evaluated retrospectively. Data was abstracted from medical records including patient charts, laboratory data, and imaging. Toxicities were recorded using Common Terminology Criteria 3.0. Response was recorded according to modified RECIST (mRECIST) criteria. RESULTS: Seventeen patients received 33 treatments with Y-90 radioembolization. A majority (65%) received TheraSphere with a minority (35%) receiving SIR-Spheres. The median treatment activity delivered was 1.725 gBq (range, 1.4-2.5 gBq). The median treatment dose delivered was 100 Gy (range, 90-120 Gy). The median lung shunt fraction was 2.02% (range, 1.5-4.1%). The most common clinical toxicity among all patients was nausea and vomiting (59%), primarily grade 1 and 2. Other post-treatment findings included abdominal pain (29%), fatigue (53%), and weight loss (18%). One patient developed a grade 5 gastric ulcer after the treatment. A clinical benefit, defined as patients achieving complete response (CR), partial response (PR) or stable disease (SD), was seen in 48% of patients. PR was seen in 24% of cases; progressive disease (PD) was noted in 35%. Patients survived for a median of 8.4 months (range, 1.3 to 21.1 months) after the first radioembolization treatment. Median survival after Y-90 treatment was 8.4 months among patients treated TheraSphere as compared with 7.8 months in patients treated with SIR-Spheres. The mean overall survival from the time of diagnosis was 11.7 months (range, 3.4 to 43.2 months). CONCLUSIONS: For patients with unresectable HCC, Y-90 radioembolization is a safe and well-tolerated procedure. Our experience suggests that a significant percentage of patients achieve clinical benefit including many with PR. Survival after treatment from this single-center, transplant center is in line with prior reports. Prospective, randomized data is required to compare radioembolization with other therapies including chemoembolization and systemic therapy with sorafenib.